Predictors of functional capacity in patients with pulmonary hypertension - Plácido, Rui (2015)
© 2015 Plácido R, et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.